Réhabilitation esthétique et fonctionnelle globale par la prothèse fixée d’un cas de bruxisme - HASSEN , Narjes; OUALHA , Ramy; OUALHA , Lamia; BOUKOTTAYA , Samir; DOUKI, Nabiha (International Arab Journal of Dentistry (IAJD), 2014)
Bruxism is an unconscious behavior characterized by contractions of the masticatory muscles outside the physiological functions. The dentist is required to manage the oral consequences of bruxism; the most remarkable one is dental wear. When the dental degree of damage becomes important, a total fixed prosthetic treatment must be conceived. The prosthetic rehabilitation aims at restoring all the occlusal functions (centering, guidance), to allow the entire masticatory system to operate with minimal constraints. It must redefine esthetic criteria, reestablish a good functional occlusal stability and optimize the functions of the masticatory system. These basic concepts are illustrated by the presentation of a clinical case of a patient suffering from bruxism.